Catholic Charismatic Renewal Movement and Transformation of Life. Issue 2 (2nd July 2016) - Alva, Reginald
Abstract : Transformation of life is at the heart of Christianity. Ongoing conversion is a part of a Christian's life. Baptism signals death to an old way of life and the embracing of new life. Christians make a sequence of choices to follow Christ radically, and therefore to accept a counter cultural stance. The societal pressures challenge a Christian living in opposition to the norms of the majority. As modernization and secularization gain strength, spiritual values are threatened. The Catholic Charismatic Renewal Movement (CCRM), which began in 1967, assists a counter cultural stance. It focuses on conversion and transformation of life by having a deep experience of the Holy Spirit, namely baptism in the Holy Spirit. The CCRM is active in more than 235 nations and millions of people take part in its programmes. This article examines the role of the CCRM in helping people to achieve a transformation of life in secularized society. The article uses Church documents, the Magisterium, the documents of the CCRM and some testimonies.